Improved Electric Strength and Space Charge Characterization in LDPE Composites with Montmorillonite Fillers. (20th November 2013) - Liao, Ruijin; Bai, Ge; Yang, Lijun; Cheng, Huanchao; Yuan, Yuan; Guan, Jianxin
Abstract : Space charge distribution and breakdown strength were investigated in composites of low density polyethylene (LDPE) and various contents of montmorillonite (MMT). The disperse performance of MMT in LDPE was observed with scanning electron microscopy (SEM) and X-ray diffraction. For MMT concentration of 1 wt%, the better intercalation of LDPE into MMT interlayers and the tighter interface structure between polymer-filler were observed, relative to MMT concentration of 3 and 5 wt%. Space charge profiles were obtained using the pulsed electroacoustic (PEA) method. Less space charge accumulated in the LDPE/MMT with MMT content of 1 wt% than that in pure LDPE, and space charge in the central of LDPE/MMT was much more uniformly. On the other hand, when MMT concentration was up to 3 and 5 wt%, large amounts of heterocharges were accumulated in the sample bulk. In MMT doped samples the dielectric strength increased up to a maximum at 1 wt% loading, and then decreases at 3 and 5 wt%.